PENGARUH PENGGUNAAN MATERIAL RECLAIMED ASPHALT PAVEMENT (RAP) SEBAGAI MATERIAL PENYUSUN TERHADAP KARAKTERISTIK CAMPURAN BERASPAL BARU AC-BC (ASPHALT CONCRETE-BINDER COURSE) - Muhammad Rizal Permadi; Retno Handayani Prastyaningrum; Bagus Hario Setiadji; Supriyono Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
The roads construction process in Indonesia mostly used conventional method, it used a lot of aggregates and asphalt in large numbers. If it’s done continuously will cause some environmental problems. One of the technology that applied asphalt recycling is Reclaimed Asphalt Pavement (RAP). Reclaimed Asphalt Pavement is a used material from hot mix cold milling process . This study has been done in order to make AC-BC mix used RAP from damaged pavement (cracking and bleeding). The percentages used of RAP were 23%, 27% and 31%. 23% RAP with 6,19% of optimum asphalt content (bleeding type) produced Gmb 2,358; VMA 16,484%; VFA 73,772%; VIM 4,933%; stability 982,04 kg; flow 2,895 mm; MQ 332,779 kg/mm; and film thickness 9,75 µm. 23% RAP with 6,25% of optimum asphalt content (cracking type) Gmb 2,403; VMA 15,812%; VFA 77,385%; VIM 4,174%; stability 992,082 kg; flow 2,88 mm; MQ 338,652 kg/mm; and film asphalt thickness 9,92 µm. Based on the research that’d been done mixture with 23% of RAP is more stable than 27% and 31% in the same condition it can be seen from the stability value which is greater enough and the flow that lower enough.